NU Studies: Sebuah Upaya Meneguhkan Posisi Penulisnya - Mujiburrahman, Mujiburrahman (Studia Islamika, 2006)
Book Review: Ahmad Baso, NU Studies: Pergolakan Pemikiran antara Fundamentalisme Islam dan Fundamentalisme Neo-Liberal (Jakarta: Erlangga, 2006), 510 halaman + xxi.Although this book is entitled NU Studies, which gives one the impression that it constitutes an academic study about the ideological developments within NU, it is in fact more so an effort on the part of the author to advocate and strengthen his own position and opinions against those who hold opposing ideas, be they within NU or outside of the organization. As a result of this aim, it's not surprising that many contradictions and inconsistencies have made their way into the book. This is mainly because the author has employed a strategy of rejecting ideas from his opposition, often without basis, whilst promoting his own views which he considers to be appropriate with the ideology of Ahlussunnah Waljamaah as held by NU.DOI: 10.15408/sdi.v13i3.564